Morphological allometry of three hymenopteran ectoparasitoids of stored-product insect pests - Kento HIRATA; Kôji SASAKAWA (European Journal of Entomology)
Allometric analysis provides an insight into the function and diversification mechanisms of body parts in organisms. The allometry and variability in size of various body parts of three hymenopteran species, Anisopteromalus calandrae (Howard), Anisopteromalus quinarius Gokhman & Baur, and Heterospilus prosopidis Viereck, which are solitary ectoparasitoids of stored-product insect pests, were studied. The relationship between many of the traits measured and body size is negatively allometric, others were isometric, and none were positively allometric. The two species of Anisopteromalus were less variable in size than H. prosopidis and there were intersexual differences in both species of Anisopteromalus. Although the patterns in these differences are complex and difficult to interpret from an ecological perspective, based on information on their behaviour it is hypothesized that stabilizing selection is associated with the negative allometry of two traits: ovipositor length in at least two species and male leg length in both species of Anisopteromalus. This hypothesis is supported by the lower variability in the size of these body parts compared to other body parts examined in this study, which is typical of traits subject to stabilizing selection.